A case of oropharyngeal Ureaplasma urealyticum infection in a human immunodeficiency virus positive bisexual male co-infected with human papilloma virus and Treponema pallidum. (10th January 2018) - Suri, Nazneen Arif; Sebastian, Sujeesh; Yadav, Deepika; Khanna, Neena; Dhawan, Benu
Abstract : Introduction. Management strategies for sexually transmitted infections (STIs) in their extragenital forms address Neisseria gonorrhoeae and Chlamydia trachomatis alone; whereas increased rates of isolation of other STI agents have been reported from various parts of the world. Their extragenital presence as a reservoir of infection emphasizes the need to screen and treat them at these sites. Case presentation. A 35-year-old human immunodeficiency virus 1 infected bisexual male presented with urethral discharge and multiple ano-genital warts. He was reactive for the venereal disease research laboratory (VDRL) test. He tested positive for Ureaplasma spp. both by culture and PCR at urethral and oropharyngeal sites, but was negative at the rectal site. The patient was successfully treated with doxycycline and penicillin, and was followed up with a test of cure at 6 weeks. Conclusion. In view of the disseminating infections that can be caused by Ureaplasma spp., it makes it important to screen for these infections even at non-genital sites, especially in the immunocompromised. STIs may be asymptomatic and can serve as a reservoir of infection in a population. This report should promote all efforts to formulate guidelines for extragenital screening of all STI pathogens.